2007
DOI: 10.1086/509769
|View full text |Cite
|
Sign up to set email alerts
|

Active Region Loops: Temperature Measurements as a Function of Time from JointTRACEandSOHOCDS Observations

Abstract: In this paper, we aim to quantitatively investigate the structure and time variation of quiescent active region loop structures. We coordinated a joint program of observations (JOP 146) using TRACE, to obtain high-cadence EUV images, and SOHO CDS, to obtain spectroscopic data. Loop intensities are used to determine temperature as a function of time for a single loop, taking full account of the background emission. In many locations, the emission measure loci are consistent with an isothermal structure. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
(31 reference statements)
4
25
0
Order By: Relevance
“…Our SOHO CDS observations showed that the majority of the observed warm loops are long-lasting, i.e. do not appear to cool down or heat up significantly over timescales of hours Cirtain et al 2007). Our results are in contrast to those obtained by Warren et al (2003); Ugarte-Urra et al (2006Viall & Klimchuk (2011), although they do not necessarily imply steady heating for the single structures.…”
Section: )mentioning
confidence: 76%
See 1 more Smart Citation
“…Our SOHO CDS observations showed that the majority of the observed warm loops are long-lasting, i.e. do not appear to cool down or heat up significantly over timescales of hours Cirtain et al 2007). Our results are in contrast to those obtained by Warren et al (2003); Ugarte-Urra et al (2006Viall & Klimchuk (2011), although they do not necessarily imply steady heating for the single structures.…”
Section: )mentioning
confidence: 76%
“…Most warm loops were found to be nearly isothermal in their cross-section, with filling factors close to one at their base (Del Zanna 2003a;Cirtain et al 2007). Our results have so far been largely confirmed by Hinode EIS and SDO AIA observations.…”
Section: Introductionmentioning
confidence: 96%
“…In the least, contamination from diffuse background and/or foreground emission is present, or the plasma is multithermal (e.g., Schmelz et al 2005;Schmelz & Martens 2006;Cirtain et al 2007;Schmelz et al 2007aSchmelz et al , 2008Aschwanden et al 2008;Schmelz et al 2009a;Terzo & Reale 2010;O'Dwyer et al 2010), or there is a contribution from low-intensity high-temperature component (e.g. Reale et al 2009a,b;Schmelz et al 2009b,c).…”
Section: Temperature Diagnostic Using Cifrmentioning
confidence: 99%
“…Therefore, in this approach it is more adequate to use many filters or lines in terms of differential emission measure distributions DEM(T )/dT (Pottash et al, 1964;Sylwester et al, 1980). Extended discussion of the DEM versus isothermal approximation can by found, for example, in Schmelz et al (2001), Cirtain et al (2007) and references therein.…”
Section: Introductionmentioning
confidence: 99%